2009
DOI: 10.1111/j.1365-2125.2009.03402.x
|View full text |Cite
|
Sign up to set email alerts
|

Triple antiplatelet therapy vs. dual antiplatelet therapy in patients undergoing percutaneous coronary intervention: an evidence‐based approach to answering a clinical query

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT?• Different strategies have been evaluated for their efficacy in reducing stent thrombosis and restenosis in patients undergoing percutaneous coronary intervention (PCI).• Triple antiplatelet therapy is one such strategy that has been shown to improve the efficacy outcomes associated with PCI.• Cilostazol is an antiplatelet agent that is being prescribed as a component of triple-therapy regimen in various centres in our country, and the beneficial effect of cilostazol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…This is due to cilostazol inhibiting the progression of carotid intima-media thickness and thus producing an additional anti-proliferative effect, regardless of the fact that DAT itself is a potent therapy (23,2931). Notably, the significantly reduced rate of MACE in the long-term follow-up subgroup is inconsistent with the findings of two previous meta-analyses, which indicated that there was no difference in the clinical outcomes of MACE between DAT and TAT treatment groups (11,28). A potential reason for the discrepancy may be the limited number of included studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This is due to cilostazol inhibiting the progression of carotid intima-media thickness and thus producing an additional anti-proliferative effect, regardless of the fact that DAT itself is a potent therapy (23,2931). Notably, the significantly reduced rate of MACE in the long-term follow-up subgroup is inconsistent with the findings of two previous meta-analyses, which indicated that there was no difference in the clinical outcomes of MACE between DAT and TAT treatment groups (11,28). A potential reason for the discrepancy may be the limited number of included studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Over the past decade, numerous studies have indicated that the use of adjunctive antiplatelet agents has resulted in decreased stent-associated thrombosis and is important in improving the final outcomes of PCI (27). Two meta-analyses by Tamhane et al (11) and Singh et al (28) also indicated that patients treated with TAT exhibited a lower restenosis rate than those treated with DAT (11,28). However, these meta-analyses did not provide reliable results demonstrating the differences in the clinical outcomes between TAT and DAT for patients with CHD undergoing PCI with coronary stent implantation.…”
Section: Discussionmentioning
confidence: 97%
“…Two meta-analyses [41,42] included only 4–5 RCTs with 1,457–1,597 patients. The meta-analysis by Tamhane et al [43] included 10 RCTs (7 trials as a full text and 3 trials presented at scientific meetings) with 2,809 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with recent meta-analyses showing that cilostazol did not reduce mortality or MI at any point during the follow-up between 6 months and 2 years. 22, 23 Several studies have shown that adding cilostazol to DAT after DES implantation decreased angiographic restenosis compared with DAT. 9,23,24 This beneficial effect of cilostazol was more prominent in patients with long coronary lesions and in diabetic patients.…”
Section: Study Limitationsmentioning
confidence: 99%